Magnetic Resonance Imaging Evaluation in Patients with Linear Morphea Treated with Methotrexate and High-Dose Corticosteroid - Mohammad Shahidi-Dadras; Fahimeh Abdollahimajd; Razieh Jahangard; Ali Javinani; Amir Ashraf-Ganjouei; Parviz Toossi (Dermatology Research and Practice)
Background. Morphea is an inflammatory disease of the connective tissue that may lead to thickening and hardening of the skin due to fibrosis. The aim of this study was to document magnetic resonance imaging (MRI) changes in patients with linear morphea who were treated with methotrexate (MTX) and high-dose corticosteroid. Methods. This study was conducted on 33 patients from the outpatient’s dermatology clinic of our institute, who fulfilled the inclusion criteria. Patients received 15 mg/week of MTX and monthly pulses of methylprednisolone for three days in six months. The effectiveness of the treatment was evaluated by MRI, modified LS skin severity index (mLoSSI), and localized scleroderma damage index (LoSDI). Results. All parameters of mLoSSI and LoSDI including erythema, skin thickness, new lesion/lesion extension, dermal atrophy, subcutaneous atrophy, and dyspigmentation were also noticeably improved after treatment. Subcutaneous fat enhancement was the most common finding in MRI. MRI scores were significantly associated with clinical markers both before and after the treatment with the exception of skin thickness and new lesion/lesion extension which were not associated with MRI scores before and after the treatment, respectively. Limitations. The lack of correlative laboratory disease activity markers, control group, and clearly defined criteria to judge the MRI changes. Conclusion. MRI could be a promising tool for the assessment of musculoskeletal and dermal involvement and also monitoring treatment response in patients with morphea.